Molar incisor hypomineralization (MIH): conservative treatment management to restore affected teeth - Camila Maria Bullio FRAGELLI; Juliana Feltrin de SOUZA; Fabiano JEREMIAS; Rita de Cássia Loiola CORDEIRO; Lourdes SANTOS-PINTO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The purpose of this study was to evaluate the 12-month clinical performance of glass ionomer restorations in teeth with MIH. First permanent molars affected by MIH (48) were restored with glass ionomer cement (GIC) and evaluated at baseline, at 6 and at 12 months, by assessing tooth enamel breakdown, GIC breakdown and caries lesion associations. The data were analyzed using the chi-square test and actuarial survival analysis. The likelihood of a restored tooth remaining unchanged at the end of 12 months was 78%. No statistically significant difference was observed in the association between increased MIH severity and caries at baseline (p > 0.05) for a 6-month period, or between increased MIH severity and previous unsatisfactory treatment at baseline (p > 0.05) for both a 6- and 12-month period. A statistically significant difference was observed in the association between increased MIH severity and extension of the restoration, involving 2 or more surfaces (p < 0.05) at both periods, and between increased MIH severity and caries at baseline (p < 0.05) at a 12-month period. Because the likelihood of maintaining the tooth structures with GIC restorations is high, invasive treatment should be postponed until the child is sufficiently mature to cooperate with the treatment, mainly of teeth affected on just one face.